Jan Bernard Bonifacio 1517-1597 / Jan Michał Krzemiński. - Krzemiński, Jan Michał (1943-2010) (Biblioteka Gdańska Polskiej Akademii Nauk, 1997)
Folder wystawy, która miała miejsce w Hallu PAN Biblioteki Gdańskiej 24.03-25.04.1997 r.